Aged Nicotinamide Riboside Kinase 2 Deficient Mice Present an Altered Response to Endurance Exercise Training - Deloux, Robin; Tannous, Cynthia; Ferry, Arnaud; Li, Zhenlin; Mericskay, Mathias (Frontiers in Physiology, 2018)
Background: Skeletal muscle ageing is marked by the development of a sarcopenic phenotype, a global decline of muscle energetic capacities and an intolerance to exercise. Among the metabolic disorders involved in this syndrome, NAD metabolism was shown to be altered in skeletal muscle, with an important role for the NAMPT enzyme recycling the nicotinamide precursor. An alternative pathway for NAD biosynthesis has been described for the nicotinamide riboside vitamin B3 precursor used by the NMRK kinases, including the striated muscle-specific NMRK2. Aim: With this study, our goal is to explore the ability of 16-month-old Nmrk2 -/- mice to perform endurance exercise and study the consequences on muscle adaptation to exercise. Methods: 10 control and 6 Nmrk2 -/- mice were used and randomly assigned to sedentary and treadmill endurance training groups. After 9 weeks of training, heart and skeletal muscle samples were harvested and used for gene expression analysis, NAD levels measurements and immunohistochemistry staining. Results – Endurance training triggered a reduction in the expression of Cpt1b and AcadL genes involved in fatty acid catabolism in the heart of Nmrk2 -/- mice, not in control mice. NAD levels were not altered in heart or skeletal muscle, nor at baseline neither after exercise training in any group. Myh7 gene encoding for the slow MHC-I was more strongly induced by exercise in Nmrk2 -/- mice than in controls. Moreover, IL-15 expression levels is higher in Nmrk2 -/- mice skeletal muscle at baseline compared to controls. No fiber type switch was observed in plantaris after exercise, but fast fibers diameter was reduced in aged control mice, not in Nmrk2 -/- mice. No fiber type switch or diameter modification was observed in soleus muscle. Conclusion: In this study, we demonstrated for the first time a phenotype in old Nmrk2 -/- mice in response to endurance exercise training. Although NMRK2 seems to be predominantly dispensable to maintain global NAD levels in heart and skeletal muscle, we demonstrated a maladaptive metabolic response to exercise in cardiac and skeletal muscle, showing that NMRK2 has a specific and restricted role in NAD signaling compared to the NAMPT pathway.